Effects of Urbanization on Digit Length, Second-to-fourth Digit Ratio (2D - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:Urbanization and its attendant lifestyle modifications have been shown to affect body compositions, anatomical variables, and phenotypes, and body composition and phenotypes are important determinants of blood pressure. The present study aimed at investigating the effect of urban dwelling on digit length, second-to-fourth digit ratio (2D:4D), and blood pressure in a sample of urban and rural population of Hausa ethnic group in Kano, Nigeria.Materials and Methods:The study design was cross-sectional and included 465 (266 males and 199 females) persons of Hausa ethnic group residing in Kano. The mean age was 34.4 years for males and 32.0 years for females. Systematic random sampling technique was employed for subject recruitment. Height, weight, digit lengths, and digit ratios were obtained using standard anthropometric techniques. Blood pressure was measured following standard clinical procedure.Results:The results showed that both systolic and diastolic components of blood pressure were significantly higher in urban than in rural participants. While the length of the ring (4th) finger was significantly higher in the rural participants, there was no statistically significant rural–urban difference in the length of the index (2nd) digit. 2D:4D was significantly lower in the rural than in urban participants. The rural–urban difference in the digit ratio was more marked in the male participants than in females and more marked in the right hand than left hand.Conclusion:Diastolic and systolic components of blood pressure are significantly higher in the urban participants. Urban–rural difference in 2D:4D was observed among Hausa population.